Donor‐derived infections in the United States: Opportunities to learn from the Disease Transmission Advisory Committee's experience - Danziger‐Isakov, Lara; La Hoz, Ricardo M; Wolfe, Cameron R; Blumberg, Emily A (Transplant infectious disease, 2024)
The Disease Transmission Advisory Committee (DTAC) of the Organ Procurement and Transplantation Network focuses on issues related to the transmission of disease through organ transplantation. Providing a review of potential cases of transmission, translating aggregate data into actionable education and guidance for the transplant community, and providing input for policy development, DTAC aims to improve the safety of organ transplantation through a reduction in donor‐derived transmission events. Through its nearly 20‐year history, DTAC has provided education, guidance, and policy, addressed numerous emerging infections, and continuously focused on the community's understanding of risk assessment related to donor‐derived transmission. By updating the DTAC mission to both decrease transmission and safely expand the donor pool with additional guidance to safely use organs previously not considered for transplantation due to transmission concerns, the Committee's role will remain critical.